Granulomatous Polyangiitis Refractory to Induction With Rituximab in 3 Patients - Nouran Eshak MD; Grace Ehikhueme MD; Malvika Ramesh MD; John Pixley MD (SAGE Publishing, 2024)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are a group of immune-mediated diseases characterized by inflammation of small vessels, leading to endothelial injury with subsequent tissue damage. Current guidelines recommend induction therapy with rituximab over cyclophosphamide for severe disease activity. In this case series-based review, the authors discuss 3 cases of granulomatosis with polyangiitis (GPA) with proteinase-3 (PR3) disease that deteriorated following induction therapy with rituximab combined with mycophenolate mofetil and high-dose steroids. All 3 patients subsequently required salvage therapy with cyclophosphamide. Our experience suggests there is a temporal window where induction with rituximab is not fully effective, and deterioration or death can ensue. Expert recommendations do not offer a preferential protocol for induction with either rituximab or cyclophosphamide, with some even using a combination of both.